ForestEcoSecurity - Management methods and technology for young boreal forests for adaptation to sustainable forest management goals in a changing climate - Nuutinen, Yrjö; Bergström, Dan; Routa, Johanna (Luonnonvarakeskus, 2024)
Focusing on young forest management, we summarize the Nordic forestry objectives, their target measures and current state of the forests. Based on the Nordic Boreal Forestry area study results, we review the current young stand management systems. Finally, we analyze the strengths and weaknesses of the systems to assess the roadmap for further development.
Keywords: forest management; boreal forests; sustainable forest management